Students’ Perception on Ideal Age of Marriage and Childbearing - Mohanambehai Subranmiam; Kuswandewi Mutyara; Hanom Husni Syam (Althea Medical Journal, 2015)
Background: Early-age marriage is still common in Indonesia, especially in the rural areas. There are many negative effects of the marriage; the young brides may get lower education, lower social status, minimum reproduction control, higher maternal mortality, higher domestic violence rate and others. Thus, this study is conducted to identify the students’ perception on the ideal age of marriage and childbearing.Methods: A cross-sectional descriptive study was conducted from June to September 2013 in Jatinangor using secondary data from Jatinangor Cohort Survey Team. The data comprised two hundred and twenty students from Jatinangor Senior High School and PGRI Vocational School. A hundred and ten males and a hundred and ten females were chosen by random sampling. Questionnaires were given after the written informed consent was obtained from the students.Results: The results showed 74.55% of the students chose 19¬–24 years old as the ideal age of marriage for a woman and 68.64% students chose 25–30 years old as the ideal age of marriage for a man. Moreover, forchildbearing, 25–30 years old was chosen to be the ideal age for both man and woman. The percentage of students agreed to this was 74.55% and 54.09% respectively.Conclusions: Majority of the students agreed on 19–24 years old and 25–30 years old as the ideal age of marriage for woman and man respectively. For childbearing, 25–30 years old was concluded as the ideal agefor both genders. [AMJ.2015;2(4):591–6] DOI: 10.15850/amj.v2n4.661